Fluor-rewitzerite, [(H2O)K]Mn2(Al2Ti)(PO4)4(OF)(H2O)10⋅4H2O, a new paulkerrite-group mineral, from the Hagendorf-Süd pegmatite, Oberpfalz, Bavaria, Germany - Hochleitner, Rupert; Grey, Ian E; Kampf, Anthony R; Boer, Stephanie; MacRae, Colin M; Mumme, William G; Wilson, Nicholas C (European journal of mineralogy (Stuttgart), 2024)
Fluor-rewitzerite, [(H2O)K]Mn2(Al2Ti)(PO4)4(OF)(H2O)10⋅4H2O, is a new monoclinic member of the paulkerrite group, from the Hagendorf-Süd pegmatite, Oberpfalz (Upper Palatinate in English), Bavaria, Germany. It occurs on the walls of vugs in corroded zwieselite, in association with Zn- and Al-bearing earlshannonite, fluorapatite, jahnsite-(CaMnMn) and Al-rich strunzite. Fluor-rewitzerite forms clusters of colourless stubby prisms up to 0.1 mm long that are flattened on {010}; elongated along [100]; and show the forms {100}, {010}, {001}, {111} and {111‾}. Twinning occurs by 2-fold rotation about c. The measured density is 2.42(2) g cm-3. Optically, fluor-rewitzerite crystals are biaxial (+), with α = 1.569(3), β = 1.582(3), γ = 1.602(3) (white light) and 2V(meas) = 78(1)°. The empirical formula from electron microprobe analyses and structure refinement is A1[(H2O)0.85K0.15]Σ1.00A2(K1.00) M1(Mn2+1.50Mg0.09Fe2+0.41)Σ2.00M2+M3(Al1.70Ti4+0.89Fe3+0.42)Σ3.01(PO4)3.99X(O1.09F0.92)Σ2.01(H2O)10⋅4.12H2O. Fluor-rewitzerite has monoclinic symmetry with space group P21/c and unit-cell parameters a = 10.407(1) Å, b = 20.514(2) Å, c = 12.193(1) Å, β = 90.49(2)°, V = 2603.0(4) Å3 and Z = 4. The crystal structure was refined using synchrotron single-crystal data to Robs=0.058 for 6186 reflections with I>3σ(I). Fluor-rewitzerite is the fluoride analogue of rewitzerite, with F dominant over OH at the X sites of the general formula A1A2M12M22M3(PO4)4X2(H2O)10⋅4H2O.